Where Women Prevail 2001 Census and Female Heads of Households - ASHISH BOSE (Economic and Political Weekly June 3, 2006, 2006)
This article examines the detailed data on households as per the census figures of 2001, in particular, women-headed households. The reasons behind women heading households range from sociological to economic.